1972
DOI: 10.1039/f19726801200
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic investigation of the lanthanide(III)-nitrate complexation reaction

Abstract: Using ultrasonic relaxation technique the kinetics of lanthanide nitrate complexation were investigated in the presence of excess nitrate ion for NdUII), Gd(III), Dy(II1) and Er(II1). The absorption spectra could most simply be interpreted in terms of a double relaxation. At 25°C the complexation rate constants, kS4, were 1.8 x lo8 s-' for Nd(II1) and 0.6 x los s-l for Er(1II). These rate constants were compared with those from earlier lanthanide complexation studies to interpret the overall complexation mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1973
1973
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(17 citation statements)
references
References 1 publication
1
16
0
Order By: Relevance
“…This factor, together with the reduction in the charge and number of ions in these solutions, accounts for the fact that the rare earth nitrate In y ± values are not as high as the chloride and perchlorate values. This displacement of rare earth Ion Inner sphere water by the nitrate Ion Is also observed in ultrasonic absorption experiments (15,16). If a rare earth nitrate solution is diluted, the amount of outer sphere complexes should increase relative to the amount of Inner sphere complexes.…”
Section: Resultsmentioning
confidence: 52%
See 2 more Smart Citations
“…This factor, together with the reduction in the charge and number of ions in these solutions, accounts for the fact that the rare earth nitrate In y ± values are not as high as the chloride and perchlorate values. This displacement of rare earth Ion Inner sphere water by the nitrate Ion Is also observed in ultrasonic absorption experiments (15,16). If a rare earth nitrate solution is diluted, the amount of outer sphere complexes should increase relative to the amount of Inner sphere complexes.…”
Section: Resultsmentioning
confidence: 52%
“…The symmetry of the uncomplexed nitrate Ion In aqueous solution is known to be reduced from the expected D3h symmetry, and this reduction In symmetry has been interpreted in terms of the formation of one fairly strong hydrogen bond between the nitrate ion and a water molecule (4). The rare earth nitrates form appreciable amounts of inner sphere complexes (1-3, 5,13,15,16), especially at high concentrations. The formation of inner sphere complexes will result In the displacement of water from the rare earth ion's Inner sphere, and will reduce the charge on the rare earth ion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is little literature in favour of the assumption that the molecular motions are slowed up in the outer solvation sphere [37,39], mainly because of the absence of direct experimental evidence. Since it is likely that strong electric fields, of the order of 104-105 volt/cm, are still present at a distance from the ion of ~ 4 A, a reduction of the mobility of solvent molecules is to be expected [40].…”
Section: 5mentioning
confidence: 97%
“…To improve the efficacy of these processes the knowledge on behavior of lanthanide ions in acidic solution is of great importance. Although thermo-physical, spectroscopic and other properties of rare-earth chlorides, perchlorates and nitrates have been studied by quite a number of groups [21][22][23][24][25][26][27][28][29][30], to the best of knowledge of the authors, such study as a function of acid (ionic) strength of aqueous medium has not been reported so far. The authors therefore felt it worthwhile to explore the behavior of a typical lanthanide ion in medium of nitric acid of varying strength which essentially changed the ionic strength of the medium.…”
Section: Introductionmentioning
confidence: 99%